Radiochemical capabilities for astrophysics experiments at the national ignition facility - Despotopulos, John D.; Gharibyan, Narek; Moody, Kenton J.; Yeamans, Charles; Velsko, Carol; Shaughnessy, Dawn A. (Frontiers in Physics, 2022)
The Nuclear and Radiochemistry Group at Lawrence Livermore National Laboratory (LLNL) has developed a suite of diagnostics and techniques that can be used for astrophysics experiments at the National Ignition Facility (NIF). Capabilities have been developed to add material to the outside of NIF hohlraum assemblies as well as to the interior of NIF target capsules or the fill gas. The ability to place very small amounts of material close to the NIF target enables activation with very large, short-pulse neutron fluxes. The Solid Radiochemistry Diagnostic can be used to collect solid debris from a NIF shot within 2 hours of the execution of a shot, and this can be analyzed for radioactive signatures with or without post-shot chemical processing. The Radiochemical Analysis of Gaseous Samples diagnostic system can be used to collect gaseous products produced during a NIF shot. Capsule doping and radiochemical analysis capabilities at NIF will be discussed. The application of these techniques to astrophysical measurements will be discussed as well as some preliminary results.